P91 Anti-IgE Therapy: An Observation in Cystic Fibrosis. (19th November 2012) - Robinson, IE; Morjaria, JB; Moon, T; Molyneux, I; Morice, AH
Abstract : Introduction: Cystic Fibrosis (CF) is characterised by the development of progressive cystic bronchiectasis. A proportion of patients have asthmatic elements which respond to conventional asthma therapy. Omalizumab (Xolair®, Novartis, UK) is a recombinant humanised monoclonal IgG which binds to IgE. We hypothesise that an IgE mediated component of airway inflammation in CF may respond to omalizumab. Methods: Seven patients mean age 31 (SD±12) years, serum IgE (30–1500), symptomatic despite maximal conventional therapy were administered omalizumab using standard dosing regimen in an open label fashion. The Asthma Control Test (ACT), Asthma Quality of Life Questionnaire (AQLQ) and FEV1 were recorded at baseline and sixteen weeks post-treatment. Days of intravenous (IV) antibiotic in the year before and during therapy were compared. Results: There was a significant improvement in the mean ACT score from 11 (±3.7) to 17 (±5.9), p=0.031. AQLQ scores pre-omalizumab 49 (±15) vs. post-omalizumab 69 (±22), p=0.156; and %FEV1 pre-omalizumab 42% (±13%) vs. post-omalizumab 45% (±14%), p=0.078 were not significantly improved. Similarly, the number of days of IV antibiotic usage declined with omalizumab treatment from 43 days (±24 days) to 25 days (±16 days) p=0.297, respectively. Discussion: This small study shows an improvement in symptom control in selected CF patients with omalizumab and other indices showed non-significant improvements, particularly IV antibiotic usage. Previous studies have demonstrated a correlation between exacerbation frequency in CF patients and the rate of decline in lung function. These findings warrant larger trials of omalizumab in 'asthmatic' CF.